Predisposing factors related to arterial hypertension in Zenú indigenous people, Córdoba, Colombia - Ocampo Rivero, Mónica Mabel (2017)
Objective: To determine the predisposing factors related to arterial hypertension in Zenúes indigenous people Córdoba, Colombia. Material and Methods: Descriptive, cross-sectional, correlational study of non-experimental design. Methodology: the WHO questionnaire called the progressive method of monitoring risk factors for NCDs (STEPS) was used in the data collection, which was adapted by the researchers. The population made up of 2300 Zenúes natives, aged between 20 and 70 years; The sample was 260, due to prejudices typical of the Zenú culture. Results: predisposing behavioral factors, such as tobacco and alcohol consumption, and diet, are significantly associated with the prevalence of hypertension (p <α (, 05)). On the other hand, biophysical factors (body mass index, waist-hip circumference), are not significantly associatively related (p> α (, 05)). Conclusions: sociodemographic factors, such as age, sex, and unconcluded basic studies, and some behavioral factors, such as smoking and alcohol consumption, and diet may be contributing to the percentage of hypertensive people in this community; However, other factors studied do not reflect a positive implication, in the predisposition of 40% of hypertensive patients in this population.